ANALISIS APLIKASI PERATURAN PENGGUNAAN PAKAIAN DIGEREJA MASEHI ADVENT HARI KETUJUH JEMAATPAKUSARAKAN BANDUNG BARAT, BERDASARKAN ULANGAN 22:5 - Ervando Tindaon; Rudolf W. Sagala (Fakultas Filsafat Universitas Advent Indonesia, 2018)
In this study, the author researching about the understanding of the use of clothing based on Deuteronomy 22: 5. The author focus this research on Pakusarakan Seventhday Adventist (SDA)Church, West Bandung.The study has a basis with four main indicators namely; Background of the rule in Deuteronomy 22:5, The purpose of the rule in Deuteronomy 22:5, Is the application of Deuteronomy 22:5 still applicable today?and Application of Deuteronomy 22:5.This research is divided into two parts, namely research theory and field research. The result of the theoretical research is the background of the rule in Deuteronomy 22:5, the application of Deuteronomy 22: 5 still applies today and how to apply theDeuteronomy 22:5 rule. This research includes 4 parts namely; (1) The background of the rule in Deuteronomy 22: 5. Some experts argue that the rule is in place is due to the practice of idolatry and the practice of transvestism; (2) The purpose of the rule in Deuteronomy 22:5. The expert states that this rule aims to maintain modesty in the proper use of clothing;(3) Does the application of Deuteronomy 22: 5 still apply today?The Rule of Deuteronomy 22:5 is a rule applicable to the Israelites of that day who had a principle of keeping holiness as God's people. And nowdays, this rule is still valid that is to maintain modesty in the use of clothing and keep holiness as God's true creation; (4) Application of Deuteronomy 22:5. The work that can be done is to use a decent and simple dress.The results of field research conducted through questionnaires distributed to 30 members of the Pakusarakan Seventhday Adventist (SDA) West Bandung.Where the questionnaire contained 15 points of statement, result a data that can be concluded that the respondents have a good understanding in answering the question indicator that authorgives.Understanding that happened because before the author gave a questionnaire, the author first gives explaination to this lesson in the form of seminars.